Malignant cylindroma in a patient with Brooke-Spiegler syndrome - Liliane Borik; Patricia Heller; Monica Shrivastava; Viktoryia Kazlouskaya (Mattioli1885, 2015)
Malignant cylindroma (cylindromatous carcinoma, cylindrocarcinoma) is the malignant counterpart of benign cylindroma. It is a rare neoplasm, more often developing in the setting of multiple pre-existing benign neoplasms. Herein we present an additional case of malignant transformation of the cylindroma diagnosed in an 83-year-old patient with known Brooke-Spiegler syndrome.